Cathodoluminescence studies of defects in coated boron nitride. (4th July 2017) - Guerch, Kévin; Dekany, Justin; Dennison, J R; Christensen, Justin; Paulmier, Thierry; Guillemet-Fritsch, Sophie; Lenormand, Pascal
Abstract: Optical emission properties of boron nitride (BN) substrates, BN with alumina (Al2 O3 ) coating, and thermally-annealed alumina-coated boron nitride (an-BN/Al2 O3 ) were investigated under electron irradiation using cathodoluminescence (CL) measurements. Tests were performed, temperatures ranging from 100 K to 300 K, with monoenergetic beams from 5 keV to 30 keV, and electron flux densities from 1 nA · cm −2 to 500 nA · cm −2 . These experiments were conducted to identify the effects of coating and thermal annealing on the nature and occupation of defect states in different samples with BN substrates. Previous studies have shown that these treatments can limit the charging of BN substrates. Consequently, thorough investigations of electron trapping and recombination processes as a function of low temperature, dose and charging/discharge were performed in order to explain the differences of electrical behaviour and compare the CL spectra of the three different samples studied. Broad features associated with the BN and sharper features resulting from the annealed alumina coating were observed. Changes in the intensity, energy, and width of the features with sample treatments were observed. Different incident beam parameters were used to associate these features with specific types of defect states. The effects of charging, temperature- and dose-dependent conductivity, and thermal annealing and aging of the samples on the CL spectra were investigated. These were used to study defect creation and occupation and to understand the predominant physical mechanisms and main structural and chemical differences between these ceramic configurations.